THE TRUTH WHICH WILL SET US ALL FREE: NATIONAL RECONCILIATION, ORAL HISTORY AND THE CONSPIRACY OF SILENCE. - Peter Read (Clio: Revista de Pesquisa Histórica, 2015)
The Australian Government, referring to thousands of Abo-riginal children allegedly stolen from their parents, responded that "the Commonwealth does not seek to defend or justify past policies and practices, but it does assert that the sature and intent of those events have been misrepresented, and that the treatment of separated Aboriginal children was essentially lawful and benign in intent..." In 1998 the Chilean government opposed the proposed trial of Gen-eral Pinochet in Spain, protesting at the grave damage it would cause to the process of democratic transition and national reconciliation. The Government of Chile believes that whatever are the intentions of those promoting the process, this does not help the intended reconcili-ation — on the contrary, they will deepen for many years the differ-ences which exist between Chileans. Are national reconciliation and oral history compatible?